Microcrystallite dimension and total active surface area of carbon electrode from mixtures of pre-carbonized oil palm empty fruit bunches and green petroleum cokes - Awitdrus,; Erman Taer,; Mohamad Deraman,; Ibrahim Abu Talib,; Ramli Omar,; Mohd. Hafizuddin Hj. Jumali,; Mansor Mohd. Saman, (Universiti Kebangsaan Malaysia, 2010)
Carbon pellets (CP) were prepared from the green pellets (GP) containing mixtures of pre-carbonized oil palm empty fruit bunches (SACG) and Green Petroleum Cokes (GPC), with the weight percentages (x) of SACG in the samples at 10%, 30%, 50%, 70% and 90%. Carbonization process to produce the CP was conducted up to 900oC using a multi steps heating profile. The interlayer spacing (d200 and d100), stack height (Lc), stack width (La,) and effective dimension L of the turbostratic crystallites (microsrystallite) in the CPs were estimated from X-ray diffraction data; d200, d100, La, L increased and Lc decreased with increasing weight percentage of SACG. The total surface area of active material of the CP (Atot) with thickness, t, estimated from Lc was found to follow the equation, Atot = [4.8086 – 0.0083x]1010 t, indicating a significant influence of the SACG content in the mixture of the green body.